Strategies of Career Women at Islamic Universities in Kalimantan in Carrying Out Household Obligations from the Perspective of Maqashid as-Syari'ah - Norcahyono Norcahyono; Muhammad Arni (Syariah: Jurnal Hukum dan Pemikiran, 2021)
Abstract: The problem of this research is the dual role of female officials (hereinafter referred to as “career women”) at Islamic universities in Kalimantan. The reasons for the research are (1) Knowing the constraints of the role played by career women at Islamic universities in Kalimantan in carrying out their obligations as housewives. (2) Revealing the role strategy of career women at Islamic universities in Kalimantan in carrying out household obligations from the Maqashid Syari'ah perspective. This research method is descriptive analytical with a normative approach. The results of the study are (1) The obstacles for career women in carrying out their obligations as housewives are not having enough productive time at home, feeling beyond their capabilities by playing multiple roles, and feeling tired. (2) The role strategy that is carried out to complete household obligations is carried out by adopting students, preparing household assistants, asking for help from family or other people, and cooperating with husbands. It can be concluded that in the perspective of Maqashid Syari'ah, the role strategy carried out by female officials in completing household obligations belongs to the Maqashid al-Hajiyyah level, namely the efforts made by career women to eliminate their difficulties in carrying out household obligations assigned to them to be the responsibility together in the family. Abstrak: permasalahan dalam penelitian ini adalah peran ganda yang dilakukan pejabat perempuan (selanjutnya disebut “wanita karir”) pada perguruan tinggi Islam di Kalimantan. Adapun alasan dari penelitian adalah (1) Mengetahui kendala peran yang dilakukan wanita karir pada perguruan tinggi Islam di Kalimantan dalam melaksanakan kewajibanya sebagai ibu rumah tangga. (2) Mengungkap Strategi peran yang dilakukan wanita karir pada perguruan tinggi Islam di Kalimantan dalam melaksanakan kewajiba dalam rumah tangga perspektif Maqashid Syari’ah. Metode yang digunakan dalam penelitian ini bersifat deskriptif analitis dengan pendekatan normatif. Hasil penelitian adalah (1) Kendala wanita karier dalam melaksanakan kewajibannya sebagi ibu rumah tangga adalah tidak memiliki waktu produktif yang cukup ketika dirumah, merasa diluar kemampuan dengan memerankan peran ganda, dan merasa kelelahan. (2) Strategi peran yang dilakukan untuk menyelesaikan kewajiban rumah tangga dilakukan dengan mengadopsi mahasiswa, menyiapkan asisten rumah tangga, meminta bantuan keluarga atau bantuan orang lain, dan bekerjasama dengan suami. Dalam perspektif Maqashid Syari’ah strategi peran yang dilakukan pejabat perempuan dalam menyelesaikan kewajiban rumah tangga tergolong pada tingkatan maqashid al-Hajiyyah yaitu upaya yang dilakukan wanita karir untuk menghilangkan kesulitannya dalam melaksanakan kewajiban rumah tangga yang dibebankan kepadanya untuk menjadi tanggungjawab bersama dalam keluarga.Kata Kunci: Peran ganda, wanita karir, maqashid as-Syari’ah